Fusobacterium nucleatum induces invasive growth and angiogenic responses in malignant oral keratinocytes that are cell line- and bacterial strain-specific - Selvaraj, Ajith; McManus, Gavin; Healy, Claire M.; Moran, Gary P. (Frontiers in Cellular and Infection Microbiology, 2024)
Fusobacterium nucleatum is an anaerobic commensal of the oral cavity recently reported to be associated with cancers of the gastrointestinal tract and oral squamous cell carcinoma (OSCC). In this study, we investigate the impact on oral keratinocytes of infection with a genetically diverse set of strains of F. nucleatum subsp. polymorphum recovered from patients with oral dysplasia (n=6). We employed H357 oral keratinocytes derived from a stage 1 OSCC and H376 cells derived from a stage 3 OSCC. Adhesion phenotypes were strain specific, with 3/6 clinical isolates examined exhibiting higher adherence to the stage 3 H376 cell line. Conversely, intracellular invasion was greatest in the H357 cells and was associated with specific transcriptional responses including autophagy and keratinization. Infection of both H357 and H376 cell lines induced transcriptional and cytokine responses linked to cancer cell migration and angiogenesis. F. nucleatum infection induced greater levels of MMP9 secretion in the H376 cell line which was associated with enhanced motility and invasion phenotypes. Additionally, the degree of F. nucleatum induced invasive growth by H376 cells varied between different clinical isolates of F. nucleatum subsp. polymorphum. Blockage of CCL5 signalling using the inhibitor metCCL5 resulted in reduced keratinocyte invasion. F. nucleatum infection also induced expression of the pro-angiogenic chemokine MCP-1 and the angiogenic growth factor VEGF-A resulting in increased capillary-like tube formation in HUVEC cells, most significantly in H376 cells. Treatment of HUVEC cells with resveratrol, a VEGF-A signalling inhibitor, significantly attenuated F. nucleatum induced tube formation. Our data indicate that the outcomes of F. nucleatum-oral cell interactions can vary greatly depending on the bacterial genotype and the malignant phenotype of the host cell.